Disruption of CCR5 signaling to treat COVID-19-associated cytokine storm: Case series of four critically ill patients treated with leronlimab - Agresti, Nicholas; Lalezari, Jacob P.; Amodeo, Phillip P.; Mody, Kabir; Mosher, Steven F.; Seethamraju, Harish; Kelly, Scott A.; Pourhassan, Nader Z.; Sudduth, C. David; Bovinet, Christopher; ElSharkawi, Ahmed E.; Patterson, Bruce K.; et al. (Journal of translational autoimmunity (Online), 2021)
Coronavirus disease 2019 (COVID-19) is associated with considerable morbidity and mortality. The number of confirmed cases of infection with SARS-CoV-2, the virus causing COVID-19 continues to escalate with over 70 million confirmed cases and over 1.6 million confirmed deaths. Severe-to-critical COVID-19 is associated with a dysregulated host immune response to the virus, which is thought to lead to pathogenic immune dysregulation and end-organ damage. Presently few effective treatment options are available to treat COVID-19. Leronlimab is a humanized IgG4, kappa monoclonal antibody that blocks C–C chemokine receptor type 5 (CCR5). It has been shown that in patients with severe COVID-19 treatment with leronlimab reduces elevated plasma IL-6 and chemokine ligand 5 (CCL5), and normalized CD4/CD8 ratios. We administered leronlimab to 4 critically ill COVID-19 patients in intensive care. All 4 of these patients improved clinically as measured by vasopressor support, and discontinuation of hemodialysis and mechanical ventilation. Following administration of leronlimab there was a statistically significant decrease in IL-6 observed in patient A (p=0.034) from day 0–7 and patient D (p=0.027) from day 0–14. This corresponds to restoration of the immune function as measured by CD4+/CD8+ T cell ratio. Although two of the patients went on to survive the other two subsequently died of surgical complications after an initial recovery from SARS-CoV-2 infection. •Leronlimab is a monoclonal antibody in clinical trials to treat the cytokine storm.•Critically ill patients received leronlimab through compassionate use and had remarkable recoveries measured objectively.•The CCR5 receptor is important in recruiting inflammatory cells mainly T cells and macrophages.•Leronlimab disrupted this signal and may have been responsible for restoration of the immune system, improved survival and decrease in IL-6.